Gastrointestinal nematodes of Paramelomys levipes and P. mollis (Rodentia: Muridae) from Papua, Indonesia and Papua New Guinea with the descriptions of three new genera and nine new species (Nematoda) - Smales, Lesley (Zootaxa, 2020)
Nematodes from four families comprising 18 species identified to species level, six to subfamily level as well as larval and adult heligmonellids and juvenile females of an undetermined family were recovered from eight individuals of Paramelomys levipes and 27 individuals of P. mollis (Muridae: Murinae: Uromys Division) from Papua New Guinea and Papua, Indonesia. Originally all the hosts were registered as P. levipes in the Australian and Bishop museum collections, but the probable identity of the host individuals was decided according to the altitude of the collection sites. A capillariid, Capillaria s. l., a putative species of the Nippostrongylinae and a small number of male and female nippostrongylins could not be identified further. The spirurid Protospirura kaindiensis had been previously reported from Sahulan Old Endemic fauna. The oxyurid Syphacia (Syphacia) dewiae n. sp. differed from all its congeners in having an oval laterally extended cephalic plate with a dorso-ventral constriction, cervical and lateral alae, a female tail up to 1400 long and a spicule up to 102 long. The remaining species, all heligmonellids included the brevistriatin Macrostrongylus ingens and 14 nippostrongylin species. Of these Hughjonestrongylus amplicauda, H. mirzai, H. singauwaensis, and Odilia mackerrasae had been reported previously in species of Paramelomys. Species of Flannerystrongylus and Parasabanema, possibly new species, could not be described further. Flannerystrongylus chisholmae n. sp., a smaller worm, differed from its congener F. abulus in having a spicule to body length ratio of 13.2% and only 6 eggs in utero. Helgenema keablei n. gen., n. sp. differed from the 44 nippostrongylin genera known to date in having a synlophe of 11– 15 small ridges and a left cuticular dilatation supported anteriorly by a single large ridge. Paramelomystrongylus dessetae n. gen., n. sp. differed from all other nippostrongylin genera in having a synlophe of 13–16 ridges with a type A carene supported by 2 hypertrophied ridges and the right lateral ridges larger than the dorsal and ventral ridges. Parasabanema sene n. sp. differed from its congener, P. szalayi, in having a synlophe of 30 ridges. Hughjonestrongylus alisoni n. sp., H. arfakiensis n. sp., H. digianiae n. sp. and H. spratti n. sp. were distinguished from all other species of Hughjonestrongylus and each other by a combination of characters including the number of synlophe ridges, 28, 21–26, 20–23, 22–25 respectively, in the mid body, spicule length, proportions of the ovejector and shape of the female posterior end. The combined helminth assemblage was dominated by heligmonellids, as has been reported for other paramelomys, with eight species as well as the oxyurid being unique to P. levipes and P. mollis. Overlapping of host habitat could account for the similarities of the nematode assemblages recorded for those species of paramelomys that have been studied.